Clinical application and nursing practice of indwelling arterial catheters in critical care medicine (重症医学科动脉留置导管临床应用及护理进展) - LI Peiyao (李佩瑶); MA Rui (马蕊); WANG Yue (王玥) (中西医结合护理)
Arterial puncture and catheterization, by providing accurate information for diagnosis and treatment, is often used in critically ill patients or those undergoing major surgery. Improper procedure and maintenance of indwelling arterial catheters may lead to complications. This paper summarized the clinical application and nursing practice of indwelling arterial catheters in critical care medicine, and provided reference for improving success of puncture and making high-quality interventions. (动脉穿刺置管常用于危重或拟行大手术患者, 有助于为治疗提供准确的信息。动脉留置导管为创伤性的治疗措施, 若操作或维护不当则容易产生并发症。本文通过阐述重症医学科动脉留置导管的临床应用及其护理进展, 以期为提高穿刺成功率和制定优质的干预策略提供理论依据。)